Mortality in Coronary Care Unit of a Tertiary Level Hospital of Bangladesh - Alam, Md Zahid; Hoque, Shabnam Jahan; Islam, Md Jubaidul; Hossain, Mohammad Shakhawat; Rahman, Aparna; Mohibullah, AKM (Bangladesh Heart Journal, 2018)
Background and objectives: Cardiovascular disease is the most common cause of death worldwide and Coronary Care Unit (CCU) plays a central role in reducing this mortality. Currently the data on mortality in CCU is very limited in our country. Our purpose of this study to provide data on mortality so that we can focus and improve the factors determining deaths in CCU. Methodology: The data of all death cases admitted in the CCU of a tertiary level hospital between 1 January 2016 and 31 December 2017 were included for assessing the data on demography, diagnosis, and comorbidities at the time of death. Results: Among 802 cases admitted in CCU in two years, 40 patients died (5%). Male was 55% and female was 45%. Most of the death occurred in their 6th decade of life, due to Non-ST-Elevation Myocardial Infarction (NSTEMI) and sepsis, within 24-hour of CCU admission.Common associated co-morbidities were DM (75%), hypertension (42.5%), CKD (27.5%), and hypokalemia (12.5%). Conclusions: The death rate is much lower in our CCU in comparison to global rate. The common cause of death is still NSTEMI. The common co-morbidities we found are DM, hypertension and CKD. Most of the deathsoccurred within 24-hour of admission. Bangladesh Heart Journal 2018; 33(1) : 28-31